2021
DOI: 10.1084/jem.20201605
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cells in tumor immunity and immunotherapy

Abstract: Tissue-resident memory T cells (TRM) represent a heterogeneous T cell population with the functionality of both effector and memory T cells. TRM express residence gene signatures. This feature allows them to traffic to, reside in, and potentially patrol peripheral tissues, thereby enforcing an efficient long-term immune-protective role. Recent studies have revealed TRM involvement in tumor immune responses. TRM tumor infiltration correlates with enhanced response to current immunotherapy and is often associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 145 publications
(206 reference statements)
7
89
0
Order By: Relevance
“…Tumor-infiltrating immune cells are the major parts of the tumor microenvironment associated with disease progress, immunotherapy response, and patient survival (49,50). We and others reported that NR0B2 has a unique function in suppressing inflammation and innate immunity in response to liver cell injury (13,21,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating immune cells are the major parts of the tumor microenvironment associated with disease progress, immunotherapy response, and patient survival (49,50). We and others reported that NR0B2 has a unique function in suppressing inflammation and innate immunity in response to liver cell injury (13,21,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Reactivated T RM cells may express cytotoxic effector molecules, including granzymes and perforin, or secrete chemokines that promote the recruitment of other leukocyte subsets, including monocytes, but also effector T cells. (8) Additionally they can loose some T RM cell markers and retention profile (Hobit, CD69, and potentially RGS1) and upregulate genes related to egress (S1pr1). (9) Thus, eventually, they can re-enter the blood circulation as "ex-T RM " cells, becoming circulating effector cells and memory T cells, thus, supporting also the systemic immune response.…”
Section: Tissue-resident Memory T Cell Subsets In the Intestinementioning
confidence: 99%
“…Although T RM cells are readily distinguished from other T cell subsets, with the increasing availability of single-cell RNA sequencing (scRNAseq) data, the heterogeneity of T RM cells in both human and mice [3,4] is becoming obvious. T RM cells are the most abundant in barrier tissues, including mucosal tissues and the skin, which represent the main entrance sites for potential pathogens [5][6][7], and may also exert critical functions in T cell-mediated anti-tumor responses [8]. On the other hand, a critical involvement of T RM cells in the induction and exacerbation of immunopathologies, including inflammatory bowel diseases (IBD) and celiac disease, has been clearly identified [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that TGF-b signaling to CD8 + T cells is essential for the differentiation and maintenance of TRM after acute infection (38)(39)(40)(41)(42)(43). When focusing on tumor immunity, TRMlike signature has often been positively associated with the capacity of TILs to control tumor (44)(45)(46)(47)(48)(49)(50)(51). It remains a mystery how to reconcile the facts that TGF-b promotes TRM, TRM limits tumor growth and TGF-b blockade improves tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…For Tgfbr2 -/stem-like T cells, defective TRM differentiation in TDLN leads to enhanced stemàeffector differentiation, elevated and sustained response to tumor vaccine. Importantly, our findings emphasize the importance of TDLN in tumor immunotherapies, i.e., TDLNs function as a reservoir to host TRM stemlike T cells.A large body of evidence has demonstrated that TRM phenotype of tumor infiltrating T cells is often associated with improved tumor control and better outcomes(51). Considering the facts that TGF-b usually promotes TRM differentiation and maintenance, it is challenging to completely explain why TGF-b inhibitors/blockers can synergize with tumor immunotherapies to improve anti-tumor immunity.…”
mentioning
confidence: 99%